Dark Moon, Eternal Sunshine: Visualizing Grief in a Seventeenth-Century Funeral Sermon - Cyril Nørgaard , Lars (Periskop – Forum for kunsthistorisk debat, 2023)
This contribution focuses on frontispieces found in printed sermons from seventeen-century Denmark. It outlines some general features of the visual programs accomplished by Hans Andreas Greys. In such frontispieces, Greys elaborated complex strategies of visual exegesis. However, he also developed frontispieces that did not limit themselves to biblical themes. One engraving, prefacing a sermon of Jesper Rasmussen Brochmand, belongs to this second series of engravings. The contribution analyzes this specific image, detailing its visual distribution of elements before turning to its portrayal of grief. This portrait involves a complex strategy and engagement with the theological language-use of the sermon.